Load transfer mechanism and reinforcement effect of segmentally yieldable anchorage in weakly consolidated soft rock. (January 2019) - Zhao, Zenghui; Ma, Qing; Tan, Yunliang; Gao, Xiaojie
Mine disasters, such as large deformation, floor heave, and roof fall, occur extremely easily in weakly consolidated soft rock strata in western China, posing enormous challenges to traditional anchorage support design. To avoid tensile failure of bolts as a result of the superposition effect of stress accumulation, a segmentally yieldable anchorage support, taking into consideration the different failure zones in surrounding rock, is presented in this paper. First, load transfer mechanisms and the process of anchorage failure are analyzed for end anchorage, full-length anchorage, and segmentally yieldable anchorage based on numerical pull-out tests. Results show that the load transfer follows a multipeak chain-like trend in the case of multipoint segmental anchorage, and that the peaks of stress attenuate slowly. Therefore, the proposed anchorage type can leverage the shear strength effectively. Furthermore, numerical models for the applications of the aforementioned three different anchoring modes to weakly consolidated soft strata are established. Results indicate that segmentally yieldable anchorage can withstand larger tensile deformation and surrounding rock deformation. Moreover, the bolt shows higher strength reservation. A combination of these characteristics is conducive to controlling deformation and damage during roadway excavation.